The effect of Orem self-care model on the improvement of symptoms and quality of life in patients with diabetes: A scoping review - Jandaghian-Bidgoli, Mohammadamin; Jamalnia, Sheida; Pashmforosh, Marzieh; Shaterian, Negin; Darabiyan, Pouriya; Rafi, Alireza (Investigación y Educación en Enfermería, 2024)
Objective: to evaluate the association of Orem self-care model improvement of symptoms and quality of life in patients with diabetes. Methods. A scoping reviewwas carried on bibliographic databases: PubMed-Medline, Scopus, SID and Magiran. The inclusion criteria encompassed studies examining the impact of the Orem self-care model on diabetic patients. Studies considered for inclusion needed to have full-text availability and be written in either English or Persian, with key words including “Models”, “Nursing”, “Quality of Life”, and “Diabetes Mellitus”. CONSORT checklist and STROBE statement were selected for quality assessment. Results. A total of 9 studies were included, all using quantitative methodology and focusing on adults or older adults. The majority of articles focused on quality of life and diabetic symptoms. 8 studies showed positive outcomes after implementation of the model. The findings indicate that this model led to an enhanced level of self-efficacy, improved quality of life, and better self-care practices among diabetic patients. Conclusion. Orem self-care model can reduce the diabetic symptoms and improve the quality of life, self-efficacy and self-care in these patients.